2004
DOI: 10.1038/sj.ejcn.1601939
|View full text |Cite
|
Sign up to set email alerts
|

Fatty-acid composition of the colostrum and serum of fullterm and preterm delivering Iraqi mothers

Abstract: Objective: To determine the lipid components of colostrum and the fatty-acid (FA) composition of the colostrum and serum of Iraqi mothers, whether their delivery be fullterm (FT) or preterm (PT). Design: A collection of colostrum and serum samples of FT and PT delivering Iraqi mothers. Setting: Mosul province (in the north of Iraq). Subjects: Colostrum and blood samples were obtained from FT and PT delivering mothers; their gestation periods were 39.2 and 32.7 weeks, respectively (age 20-40 y). Procedures: Col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 26 publications
2
4
0
Order By: Relevance
“…These vegetable oils, such as sunflower oil, contain very high concentrations of n -6 fatty acids, which would explain why the total n -6 FA did not differ between the groups. High AA concentration in BM has previously been reported in colostrum [21] and from Iran and Iraq, and reflects the high consumption of red meat [20,23].…”
Section: Discussionsupporting
confidence: 52%
“…These vegetable oils, such as sunflower oil, contain very high concentrations of n -6 fatty acids, which would explain why the total n -6 FA did not differ between the groups. High AA concentration in BM has previously been reported in colostrum [21] and from Iran and Iraq, and reflects the high consumption of red meat [20,23].…”
Section: Discussionsupporting
confidence: 52%
“…(Araya et al [32]) also found differences in maternal erythrocyte (RBC) ARA content in term and preterm delivering mothers and hypothesized that high content of maternal RBC ARA and ARA/DHA ratio may be considered as an early signal of preterm delivery. Similar observations are reported in Brazilian [33] and Iraqi mothers [34] who delivered preterm.…”
Section: Discussionsupporting
confidence: 76%
“…These LCPUFAs are found abundantly in the brain, the retina and the nervous tissue (Koletzko and Decsi, 1997;Al-Tamer and Mahmood, 2004). Evidence suggests that infants are unable to meet the EFAs requirements without being preformed in the diet (Innis, 1991;Morgan et al, 1998).…”
Section: Introductionmentioning
confidence: 99%